Djibouti : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
An important challenge for Djibouti is to implement a comprehensive strategy to promote private investment and job creation to reduce poverty. The medium-term macroeconomic outlook is dominated by the authorities' plan to launch a public investment program along with the planned construction of a new deep water seaport. The authorities have improved the expenditure control and monitored the framework, but could further enhance the transparency of public finance. Although Djibouti improved its macroeconomic database in recent years, its statistical system continues to fail owing to changes in quality, frequency, and dissemination.